Development of an omnidirectional gamma-ray imaging Compton camera for low-radiation-level environmental monitoring. (27th December 2017) - Watanabe, Takara; Enomoto, Ryoji; Muraishi, Hiroshi; Katagiri, Hideaki; Kagaya, Mika; Fukushi, Masahiro; Kano, Daisuke; Satoh, Wataru; Takeda, Tohoru; Tanaka, Manobu M.; Tanaka, Souichi; Uchida, Tomohisa; et al.
Abstract: We have developed an omnidirectional gamma-ray imaging Compton camera for environmental monitoring at low levels of radiation. The camera consisted of only six CsI(Tl) scintillator cubes of 3.5 cm, each of which was readout by super-bialkali photo-multiplier tubes (PMTs). Our camera enables the visualization of the position of gamma-ray sources in all directions (∼4π sr) over a wide energy range between 300 and 1400 keV. The angular resolution (σ) was found to be ∼11°, which was realized using an image-sharpening technique. A high detection efficiency of 18 cps/(µSv/h) for 511 keV (1.6 cps/MBq at 1 m) was achieved, indicating the capability of this camera to visualize hotspots in areas with low-radiation-level contamination from the order of µSv/h to natural background levels. Our proposed technique can be easily used as a low-radiation-level imaging monitor in radiation control areas, such as medical and accelerator facilities.